2014
DOI: 10.1007/s00436-014-4214-0
|View full text |Cite
|
Sign up to set email alerts
|

Female host sex-biased parasitism with the rodent stomach nematode Mastophorus muris in wild bank voles (Myodes glareolus)

Abstract: Abundance and prevalence of helminth infections often differ between host sexes, and are usually biased in favor of males. Relatively few cases of female-biased parasitism have been reported. We sampled bank voles in three woodland sites in N.E. Poland over 11 years at 3-4-year intervals, and assessed their parasite burdens. Prevalence and abundance of the stomach nematode Mastophorus muris were consistently higher among females. Among adult female bank voles from the two sites that showed the highest prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 89 publications
4
30
1
1
Order By: Relevance
“…Indeed, sexual differences in physiology, behavior, and evolutionary roles, have been shown to impact both the susceptibility and the exposition to different pathogens [74]. For instance, Gryzbek et al [78] evidenced that mature and reproductively active female bank voles are subject to higher exposure to helminths. Furthermore, the interplay between resistance and tolerance, the two main immune strategies implemented by a host when it is challenged by a parasite [79,80], was shown to differ substantially between male and female rodents [81].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, sexual differences in physiology, behavior, and evolutionary roles, have been shown to impact both the susceptibility and the exposition to different pathogens [74]. For instance, Gryzbek et al [78] evidenced that mature and reproductively active female bank voles are subject to higher exposure to helminths. Furthermore, the interplay between resistance and tolerance, the two main immune strategies implemented by a host when it is challenged by a parasite [79,80], was shown to differ substantially between male and female rodents [81].…”
Section: Discussionmentioning
confidence: 99%
“…The adopted statistical approach has previously been described (Behnke et al, 2008;Grzybek et al, 2015Grzybek et al, , 2014. Briefly, for analysis of For analyses of the quantitative data we used general linear models (GLM) implemented in R version 2.2.1 (R Core Development Team).…”
Section: Discussionmentioning
confidence: 99%
“…Host sex is a significant driver of parasite community, males being generally more heavily infected than females (Poulin, 1996). This pattern does not always hold (Grzybek et al, 2015), especially in horses where definitive consensus has not been reached yet (Kornaś et al, 2010; Kornaś et al, 2015; Debeffe et al, 2016). Our results suggested that horse sex did not exerted a conserved influence on worm relative abundance across species, but that mares had more consistent strongyle communities.…”
Section: Discussionmentioning
confidence: 99%
“…Host sex effect is a major driver of helminth community assemblage, male mammals being generally more frequently and more heavily parasitized (Poulin, 1996; Zuk and McKean, 1996). Although, some discrepancies exist to this general pattern (Grzybek et al, 2015). In horses, no clear consensus has been reached so far.…”
Section: Introductionmentioning
confidence: 99%